(untitled) (Research, Society and Development, 2021)
Introduction: Systemic arterial hypertension (SAH) has become one of the most worrying chronic non-communicable diseases, consisting of one of the main factors associated with the development of cardiovascular diseases and has been common in adolescents. Thus, its early detection can prevent future complications. Data from the Study of Cardiovascular Risks in Adolescents (ERICA) indicated that 24% of Brazilian adolescents had high blood pressure (BP). The elevation of BP in children and adolescents has several predisposing conditions (environmental, socioeconomic, seasonal and geographic), obesity being one of the main ones. Objective: To verify the association between nutritional status and the presence of SAH in adolescents from the cities of Teresina and Picos (Piauí, Brazil). Materials and Methods: Cross-sectional population-based study with 353 adolescents aged 10 to 19 years. demographic, socioeconomic, alcohol consumption, smoking, physical activity, blood pressure and anthropometric data. The Mann-Whitney and Chi-Square tests were used to compare continuous and categorical variables, respectively. Crude and adjusted Poisson regression was used to verify the association between nutritional status and SAH. Results: There was a proportion of overweight and obese adolescents of 17.9% and 10.0%, respectively, and a prevalence of SAH of 7.9%, with no differences between the sexes. There was a significant association, after adjustments, between SAH and obesity in the total sample and between sexes. Conclusion: The association between SAH and obesity was significant, demonstrating the importance of maintenance of adequate nutritional status in adolescence.